RADIOCHRONOLOGICAL DATA WITH U/TH METHOD IN LAGUNAL /MARINE DEPOSITS OF THE NW PELOPONNESE, GREECE. - Σταματόπουλος Λ.; Κοντόπουλος Ν.; Voltaggio, M.; Branca, M. (Bulletin of the Geological Society of Greece, 2018)
Pleistocene lagoonal sediments exposed in northwestern Peloponneses were dated by U/Th methods in Cladocora coespitosa and in Area sp. samples, were collected from the southern part of the Rion - Antirrion and western end of the Corinth grabens, which were both formed in the upper Pliocene. Our dating results, indicate a Tyrrhenian age, Upper Pleistocene, and not Lower Pleistocene ages which were reported for these sediments up until now. In particular, the absolute ages from the collected samples from Ano Kastrisi are 203.6 ±11 kyr.s, from Arachovitika 164 ± 5.8 kyr.s and from Agios George Drepanou 88.1 ± 2.3 kyr.s. The above ages belong in isotopie stages 7, 6, 5 respectively. Based on the U/Th reported ages the calculated relatives rates of uplift are, 2.8 mnvyr"1 and 4.8 mnryr"1 for the areas of Ano Kastrisi and Agios George Drepanou respectively (south-eastern margin of the Rion - Antirrion graben) and 0.4 mnryr"1 Arachovitika samples (western end of Corinth graben). The calculated different relatives rates of uplift demonstrate probably that the two grabens had a different neotectonic and paleogeographic evolution.